Intellectual Capital and Financial Performance of Quoted Manufacturing Firms - Izuchukwu Daniel Chude; Nkiru Patricia Chude; Chinedu F. Egbunike (Annals of Human Resource Management Research, 2022)
Purpose: This study examined the effect of intellectual capital on the financial performance of quoted manufacturing firms on the Nigerian Stock Exchange (NSE). The study specifically evaluated the effect of the value-added intellectual coefficient (VAIC) on Asset Turnover (ATR), Gross Profit Margin (GPM) and Return on Assets (ROA) from 2011 to 2019. Research Methodology: The research design used in the study is ex post facto. Non-probability sampling was the method of sampling that was employed in the investigation. Twenty (20) consumer products manufacturing companies that had been listed on the NSE for nine years made up the final sample. In earlier investigations, this was deemed sufficient for regression analysis. The analysis makes use of secondary data taken from the companies’ annual reports. The information spanned a nine-year span, from 2011 to 2019. Result: There is a non-significant negative effect of value added intellectual coefficient on the Asset Turnover Rate (ATR) of quoted manufacturing firms; however, there is a non-significant positive effect of VAIC on Gross Profit Margin (GPM) and Return on Assets (ROA) of quoted manufacturing firms. Limitation: The main limitation is the duration of time the study was conducted and the delisting of some firms during the period. Contribution: The research adds to the body of knowledge about developing nations, on the nexus of VAIC and financial performance. It reiterates the point that firms should emphasize intellectual capital accounting and disclosure to boost and maintain a motivated workforce and its potentially beneficial effect on firm valuation in this knowledge era.